Pemanfaatan Layanan dan Sumber Daya Informasi Perpustakaan oleh Mahasiswa UIN Imam Bonjol Padang - Rahmi, Lailatur (Jurnal Al- Ma'arif : Ilmu Perpustakaan dan Informasi Islam, 2023)
This article discusses the use of library services and information sources among undergraduate students at the Imam Bonjol Padang State Islamic University, especially those with a specialization in Library Science. The specific objective is to determine the level of awareness, accessibility, and satisfaction derived from library services and information resources; reasons, reach and challenges of using library services and information resources by undergraduate students. This study used survey research and the instrument used for data collection was a questionnaire distributed to active Library Science students both S1 and D3 at the Adab Faculty using the slovin formula for determining the sample. Descriptive analysis of responses was carried out using tables, frequency calculations, simple percentages and using the Google form. The main findings are; that Library Science students use library services and information resources to update knowledge, study for exam preparation, research purposes, complete assignments etc.; Challenges in utilizing library services and information resources are the lack of awareness of library resources, the lack of guidance to direct users to the appropriate library resource section, the provision of electronic services that have not been maximized regarding library collections; and the lack of expert assistance in finding sources of information in the library prevents students from using several sources of information such as catalogs, journals, CD-ROMs and others. This modest study also found that some of the library's information resources were not fully utilized due to lack of awareness of the resources or they did not consider them important for their studies. The recommended suggestions are the results of a questionnaire to improve library services.